2011
DOI: 10.1007/s11031-011-9249-2
|View full text |Cite
|
Sign up to set email alerts
|

Simple geometric shapes are implicitly associated with affective value

Abstract: Growing evidence suggests that the underlying geometry of a visual image is an effective mechanism for conveying the affective meaning of a scene or object. Indeed, even very simple context-free geometric shapes have been shown to signal emotion. Specifically, downward-pointing V’s are perceived as threatening and curvilinear forms are perceived as pleasant. As these shapes are thought to be primitive cues for decoding emotion, we sought to assess whether they are evaluated as affective even without extended c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 49 publications
6
65
0
1
Order By: Relevance
“…These cross preferences may be related through similar or associated semantic information. Studies have reported that simple features of geometric shapes and colors are implicitly associated with affective values and semantic impressions, and some of those semantic impressions could be connected or associated among multiple visual stimuli, such as colors and shapes …”
Section: Discussionmentioning
confidence: 99%
“…These cross preferences may be related through similar or associated semantic information. Studies have reported that simple features of geometric shapes and colors are implicitly associated with affective values and semantic impressions, and some of those semantic impressions could be connected or associated among multiple visual stimuli, such as colors and shapes …”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why, or so it has been suggested, downward-pointing triangles capture people's attention more rapidly than other geometric forms. Geometric shapes are also implicitly associated with affective value (Larson, Aronoff, & Steuer, 2012), for example, when added to faces, they affect facial judgments (faces overlaid on downward-pointing background triangles are judged more dominant; see Toet & Tak, 2013). It is easy to imagine how, during a dining experience, the shape of the visual elements (be it on the plate, the shape of the plate itself, or other elements of the dining table) could have a role in modelling certain implicit associations that the diner makes concerning the food, the overall experience, and perhaps even act to influence people's consumption behaviour.…”
Section: Conditionmentioning
confidence: 99%
“…Visch and Tan (2009) found that dynamic movement pattern in abstract animated objects influenced emotional responses; slow and direct movement generated sadness, for example, whereas high velocity movements evoked fear and surprise. In the words of Larson et al (2012; p. 410) “emotion can be effectively and implicitly communicated based on primitive geometric forms that are embedded in many common affective cues.”…”
Section: Cross-wiring In Synesthesia and Crossmodal Processing In Nonmentioning
confidence: 99%